Targeting the histone methyltransferase G9a activates imprinted genes and improves survival of a mouse model of Prader–Willi syndrome - Kim, Yuna (Nat Med, 2016)
Prader–Willi syndrome (PWS) is an imprinting disorder caused by a deficiency of paternally expressed gene(s) in the 15q11–q13 chromosomal region. The regulation of imprinted gene expression in this region is coordinated by an imprinting center (PWS-IC). In individuals with PWS, genes responsible for PWS on the maternal chromosome are present, but repressed epigenetically, which provides an opportunity for the use of epigenetic therapy to restore expression from the maternal copies of PWS-associated genes. Through a high-content screen (HCS) of >9,000 small molecules, we discovered that UNC0638 and UNC0642—two selective inhibitors of euchromatic histone lysine N-methyltransferase-2 (EHMT2, also known as G9a)—activated the maternal (m) copy of candidate genes underlying PWS, including the SnoRNA cluster SNORD116, in cells from humans with PWS and also from a mouse model of PWS carrying a paternal (p) deletion from small nuclear ribonucleoprotein N (Snrpn (S)) to ubiquitin protein ligase E3A (Ube3a (U)) (mouse model referred to hereafter as m(+)/p(ΔS−U)). Both UNC0642 and UNC0638 caused a selective reduction of the dimethylation of histone H3 lysine 9 (H3K9me2) at PWS-IC, without changing DNA methylation, when analyzed by bisulfite genomic sequencing. This indicates that histone modification is essential for the imprinting of candidate genes underlying PWS. UNC0642 displayed therapeutic effects in the PWS mouse model by improving the survival and the growth of m(+)/p(ΔS−U) newborn pups. This study provides the first proof of principle for an epigenetics-based therapy for PWS.